Distribution Of Inheritance To Non Moslems Heirs In Notary Deed From Islamic Inheritance Law Perspective - Andi Hamniza Kastury; Aynun Nurmayanti; Munsharif Abdul Chalim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The aim of this study was to: 1) To determine the position of non-Moslem heirs to the estate heir which has Islamic religion. 2) To identify and analyze how inheritance to heirs of non-Moslems in terms of the deed of Islamic inheritance law.Based on the data analysis concluded that: 1) The position of non-Moslem heirs of inheritance toward Moslem is not called heirs because of differences in religion, but he is entitled to receive a portion of the deceased's estate by his parents was borrowed. 2) The division of inheritance to heirs of non-Moslems are equal parts by the beneficiaries (women) and the other in the act of notary deed evidence obligatory will be made, each of which must be a testament that the act in order to obtain legal certainty as authentic documents binding.Keywords: Division of Heritage; Non Moslem Heirs; Notary Deed; Islamic Inheritance Law.